Prostorska analiza naravnih plezališč v Sloveniji - Rutar, Karin (Gozdarski vestnik, 2021)
Climbing in natural climbing crags is becoming an increasingly popular recreation form but evermore climbers amount to ever-growing strain on natural climbing crags. In Slovenia, at the moment there are 92 registered natural climbing crags, however, there are no systematically acquired and unified data on land use, land ownership, and definite forest functions, above all, the recreational one. In our article, the crag position was determined using field visit and based on the data from laser scanning of the surface of Slovenia. The data on climbing crags position have been combined with land use and ownership structure of the climbing crags area and forest functions map in the area. The analyses show that 88.5 % of climbing crags are situated in the forest; 76,5 % are in private ownership. Climbing crags situated in the forests with definite first level recreational function are situated on 7.6 % of Slovenian crags. The results of the analysis show that the forests in the surroundings of the natural climbing crags are not identified as forests with definite recreational function. Therefore, we suggest, that in the areas where the natural climbing crags are situated, forest functions should be reconsidered. assessed anew.
Keywords: definite recreational function; land ownership; land use; lastništvo zemljišč; naravna plezališča; natural climbing crags; poudarjenost rekreacijske funkcije; raba tal; Slovenia; Slovenija